Les Âmes fortes de Jean Giono ou l’art de la transgression - Pilorget, Jean-Paul (Romanica Silesiana)
Transgression is everywhere in Les Âmes fortes. It is present in the form of the narrative in which two opposite versions of events question the very notion of truth and well-established moral norms of judgement. As the novel of the impossible truth, Les Âmes fortes highlights the power of fiction, of lies, and of manipulation. Moral virtues are inverted in two opposite versions of the events: when generosity is increasingly showed, does it become a mark of ferocity and pride, a means of domination, or an aspect of the superior art of loosing? The Biblical values are constantly profaned in this complex novel: numerous Biblical references are quoted only to be perverted immediately afterwards. For example, in one of the two versions of her own story, one of the protagonists, Therese, manages to reach sanctity in evil, which enables her to assert her absolute domination — the main feature of the strong souls, the “âmes fortes”. Key words: Transgression, profanation, manipulation, perversion, illusion.